TEACHING INFORMATION AND COMMUNICATION TECHNOLOGIES OF THE STUDENTS IN PEDAGOGIC HIGH EDUCATIONAL ESTABLISHMETS - Havrylenko, О.М. (Journal of Information Technologies in Education (ITE), 2012)
In the article the information content, operational skills and abilities necessary for the future teachers of foreign languages in order to become proficient in use of information and communication technologies in professional activity are singled out and grounded.